(The Application of H2SO4 As Stimulant To Increase The Productivity of Oleoresin (Pinus merkusii Jungh et de Vriese) With Riil Method - Ayu Rahayu Effendi Surbakti; Ridwanti Batubara; Muhdi Muhdi (Program studi Kehutanan USU, 2014)
The Production of oleoresin is affected by the application of stimulant and time of tapping. The purpose of this research were to know the effect of H2SO4 stimulant and the time of tapping to P. merkusii and to know the H2SO4 concentration and the best time of pine tapping that gave the best of tapping. This research were carried at working area of PT. Inhutani IV, Siborong-borong in Mei – June 2013 using factorial randomized block design with two factors, i.e. the concentration of stimulant (0%, 10%, 20% and 30%) and time of tapping (3, 5 and 7 days at once). Parameter measured were production of oleoresin (gram). Result of this research showed that the application of H2SO4 stimulant on the tapping of pine trees increase considerably to oleoresin. The application of H2SO4 resulted in more than 2 – 4 times the yield of oleoresin from tree without stimulant. The concentration of H2SO4 (30%) and the time of tapping in 3 days can gave the best product of oleoresin.Key word : P. merkusii, resin, stimulant, tapping.